2020
DOI: 10.22452/mjlis.vol25no2.4
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric mapping of top papers in Library and Information Science based on the Essential Science Indicators Database

Abstract: This study analyzed top papers published in the field of Library and Information Science (LIS) published between 2009 and 2019 and included in the Web of Science (WoS) subject category “Information Science & Library Science”. Data of the 501 top papers were extracted from the Essential Science Indicators (ESI) database comprising 499 highly cited papers and 16 hot papers in the field. The distributions of document type, language of publication, scientific output, and publication of journals are reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
4
17
0
Order By: Relevance
“…The TPs produced by 41 out of 57 OIC member countries during 10 year period (2010 to 2019), obtained using scientometrics tools and techniques, comprise 7,369 HCPs and 249 HPs, all of which were articles document type and published in the English language. This study is similar to the studies conducted by Zhang et al (2018), Mofrad, Shekofteh, Kazerani (2019, Yuan and Sun (2019), and Sun and Yuan (2020), who evaluated TPs scientometrically.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The TPs produced by 41 out of 57 OIC member countries during 10 year period (2010 to 2019), obtained using scientometrics tools and techniques, comprise 7,369 HCPs and 249 HPs, all of which were articles document type and published in the English language. This study is similar to the studies conducted by Zhang et al (2018), Mofrad, Shekofteh, Kazerani (2019, Yuan and Sun (2019), and Sun and Yuan (2020), who evaluated TPs scientometrically.…”
Section: Discussionsupporting
confidence: 89%
“…The analysis of keywords showed that the research waas separated into nine clusters. Sun and Yuan (2020) studied TPs in Library and Information Science (LIS) using the ESI database from 2009 to 2019. They evaluated the LIS 501 TPs (499 HCPs and 16 HPs) in ESI.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The co-authorship network of authors is the most common kind of co-authorship network (Sun and Yuan, 2020). The network visualization of authorship in the discipline of "Augmented Reality" is depicted in Figure 5.…”
Section: Rq6 What Can Be the Network Of Author And Country Co-authors...mentioning
confidence: 99%
“…For cotton literature, bibliometric analyses of publications include research into cotton leaf curl disease (Khan et al, 2020), mapping and visualization of research topics and publishing patterns of cotton fiber (Stopar et al, 2021), soil and water conservation in the Loess Tableland-Gully Region of China (Wang et al, 2019), and advances in water-use efficiency in agriculture and sustainable water use in agriculture (Velasco-Muñoz et al, 2018a, b). Other applications of bibliometric analysis include those by Sun and Yuan that analyzed rice with fertilizer using Citespace (Sun and Yuan, 2019), identification of the top papers in world rice research (Sun and Yuan, 2020a), identification of the top papers in Library and Information Science based on essential science indicators (Sun and Yuan, 2020b), in the field of water resources (Sun and Yuan, 2020c), green and sustainable science and technology (Yuan and Sun, 2019), in agronomy (Sun and Yuan, 2021), cotton research from Plant Sciences category based on Web of Science (Yuan and Sun, 2021), and in research on maize or corn (Yuan and Sun, 2020a, b).…”
mentioning
confidence: 99%